2020
DOI: 10.1080/13685538.2020.1740200
|View full text |Cite
|
Sign up to set email alerts
|

Serum trace element and heavy metal levels in patients with sepsis

Abstract: Background and objectives: Sepsis is defined as a life-threatening organ dysfunction syndrome, which occurs when the body's immune response to infection is impaired. The aim of the present study was to investigate serum Iron, Copper, Zinco, Cobalt, Chromium, Selenium, Vanadium, Nickel, Cadmium, and Aliminium levels in patients with sepsis. Materials and methods: This prospective and observational study was conducted at a tertiary care university hospital of Turkey from 2015 to 2016, and comprised patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 34 publications
4
14
0
Order By: Relevance
“…There are some previous studies that investigated the relationship between levels of serum Cu and Zn and prognosis in sepsis or septic shock and demonstrated that the higher mortality was correlated with higher serum Cu and lower serum Zn (29,43), but this correlation was not be found in the research of Ayoglu et al in Turkey (26). In contrast, although the 28-day mortality was not signi cant difference between non-SIMD and SILVSD groups, compared with survivors with septic shock, we discovered that the increased levels of whole blood Cu and the reduced levels of whole blood Zn existed in non-survivors with septic shock, which is consistent with previous studies (29,43). After analysis of the correlations between whole blood Cu and Zn and APACHE-II score and SOFA score by Pearson line correlation, we found whole blood Cu was positively correlated with APACHE-II score and SOFA score and whole blood Zn was negatively correlated with APACHE-II score and SOFA score.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…There are some previous studies that investigated the relationship between levels of serum Cu and Zn and prognosis in sepsis or septic shock and demonstrated that the higher mortality was correlated with higher serum Cu and lower serum Zn (29,43), but this correlation was not be found in the research of Ayoglu et al in Turkey (26). In contrast, although the 28-day mortality was not signi cant difference between non-SIMD and SILVSD groups, compared with survivors with septic shock, we discovered that the increased levels of whole blood Cu and the reduced levels of whole blood Zn existed in non-survivors with septic shock, which is consistent with previous studies (29,43). After analysis of the correlations between whole blood Cu and Zn and APACHE-II score and SOFA score by Pearson line correlation, we found whole blood Cu was positively correlated with APACHE-II score and SOFA score and whole blood Zn was negatively correlated with APACHE-II score and SOFA score.…”
Section: Discussionmentioning
confidence: 93%
“…Compared with researches investigated the correlation between serum Zn and sepsis or septic shock (27,28), studies on the relationship between serum Cu and sepsis or septic shock are fewer but have shown that serum Cu levels are elevated in patients with sepsis (26). Idris et al and Manuel et al found that elevated serum Cu concentrations existed in septic patients (29,30). Cu is vital for synthesis of collagen, antioxidant response, iron transportation, acts as a cofactor for oxidative metalloenzymes and can result in anaemia, leukopenia and pancytopenia (31,32), but the potential mechanisms of higher serum Cu in sepsis remain unclear absolutely.…”
Section: Discussionmentioning
confidence: 99%
“…There are some previous studies that investigated the relationship between serum Cu and Zn levels and prognosis in sepsis or septic shock and demonstrated that the higher mortality was correlated with higher serum Cu and lower serum Zn, 19,33 but this correlation was not found in the research of Ayoglu et al in Turkey. 17 In contrast, although the 28-day mortality was not significantly different between non-SIMD and SILVSD, compared with survivors with septic shock, we discovered that the increased levels of whole blood Cu and the reduced levels of whole blood Zn existed in non-survivors with septic shock, which is consistent with previous studies.…”
Section: Dovepressmentioning
confidence: 91%
“…17 In contrast, although the 28-day mortality was not significantly different between non-SIMD and SILVSD, compared with survivors with septic shock, we discovered that the increased levels of whole blood Cu and the reduced levels of whole blood Zn existed in non-survivors with septic shock, which is consistent with previous studies. 19,33 After analysis of the correlations between whole blood Cu and Zn and APACHE-II score and SOFA score by partial correlation analysis, we found whole blood Cu was positively correlated with APACHE-II score and SOFA score and whole blood Zn was negatively correlated with APACHE-II score and SOFA score. Therefore, in this research, higher Cu concentration and lower Zn concentration may be associated with severity of multi-organ dysfunction syndrome (MODS) at admission in patients with septic shock.…”
Section: Dovepressmentioning
confidence: 92%
See 1 more Smart Citation